2018
DOI: 10.1371/journal.pone.0197137
|View full text |Cite
|
Sign up to set email alerts
|

Marginal ancestral contributions to atrial fibrillation in the Standardbred racehorse: Comparison of cases and controls

Abstract: Admissions of Standardbred racehorses (Std) to the Ontario Veterinary College Teaching Hospital (OVCTH) for treatment of atrial fibrillation (AF) began to increase in the early 1990s. The arrhythmia has been shown to have a modest heritability (h2 ≃ 0.15), with some stallions appearing as sires or sires of mares used in breeding (broodmares) of affected horses more frequently than others. The objective of this study was to determine the marginal genetic contributions of ancestors to cohorts of Std affected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…This observation is consistent with studies in horses, in which increased body mass is associated with risk of AF 51,52 . Research in Standardbred racehorses has supported a genetic basis for AF based on epidemiology and pedigree analysis 51,53,54 . Additional studies are needed to determine the role of genetics in AF in Thoroughbreds.…”
Section: Discussionsupporting
confidence: 83%
“…This observation is consistent with studies in horses, in which increased body mass is associated with risk of AF 51,52 . Research in Standardbred racehorses has supported a genetic basis for AF based on epidemiology and pedigree analysis 51,53,54 . Additional studies are needed to determine the role of genetics in AF in Thoroughbreds.…”
Section: Discussionsupporting
confidence: 83%
“…A retrospective study from Canada reported that Standardbreds were more commonly affected by AF than other breeds [64]. It was later discovered that AF is a moderately heritable arrhythmia in Standardbreds, and frequently used breeding stallions might have helped increase the incidence, though the mode of inheritance is still unknown [65,66]. A recent study investigating heritability in Thoroughbreds from Hong Kong and Australia found the heritability of AF to be low [67].…”
Section: Breed and Heritabilitymentioning
confidence: 99%
“…It is a partially heritable disease in humans and a family history of AF increases the risk of developing AF 123 . Heritability of AF has been demonstrated in Standardbred horses 124,125 where some American Standardbred lineages were more often associated with AF. Several genetic variants are linked to human AF including developmental genes like PITX2 and genes involved in metabolic stress responses 123,126,127 .…”
Section: Arrhythmogenic Mechanisms Leading To Afmentioning
confidence: 99%